A CORPUS-BASED ANALYSIS OF HEDGES AND BOOSTERS IN ENGLISH ACADEMIC ARTICLES - Takimoto, Masahiro (Indonesian Journal of Applied Linguistics, 2015)
The present study examined research articles from eight academic disciplines to measure the frequencies and functions of hedges and boosters. The quantitative results showed that hedges exceeded boosters, with philosophy articles showing a significant use of hedges and boosters. The natural science papers were underrepresented in the number of hedges and boosters. Moreover, the results indicated that the choices the writers make seem to be constrained by the discourse norms and rhetorical styles of each discipline and reflect the nature of different disciplinary characteristics. The humanities and social sciences are basically more interpretative and less abstract, a style that requires more hedges and boosters and opts for subjectivity, whereas natural sciences are typically more fact-oriented and more impersonal, which is accompanied by fewer hedges and boosters and opts for objectivity. This was confirmed by a further analysis that showed that the relative incidence of hedges of the possibility/ probability category in adjectives and adverbs was the highest in humanities and the lowest in natural sciences. Moreover, the relative incidence of hedges of the tentative cognition category in nouns and verbs was the highest in humanities and social sciences and the lowest in natural sciences.Â